Adaptive Control Design for Cargo Ship Steering with Limited Rudder Angle - Kahveci, Nazli E.; Ioannou, Petros A. (IFAC Proceedings Volumes, 2009)
Marine transportation offers a cost-effective and viable alternative to cargo aircraft, trains, and trucks in general. Traffic control in congested waterways has recently become a challenging task demanding higher accuracy in ship navigation and advanced methods for collision or grounding avoidance. Modern ship control systems call for new technologies to be applied to ship steering involving station-keeping and course-changing maneuvers. Uncertain cargo ship dynamics require robust steering control design techniques potentially reducing the effects of external conditions and minimizing path deviations in case particularly strong lateral wind or wave forces are experienced. Among the additional issues to be addressed are possible conflicts between rudder angle limitations and controller performance. We present an adaptive steering control design for uncertain cargo ship dynamics subject to input constraints while avoiding performance compromises under changing environmental conditions. Several maneuvering scenarios are simulated to verify the effectiveness of our control design approach.